Avaliação taxonômica da comunidade de ciliados peritríquios (ciliophora: oligohymenophorea: peritrichia) epibiontes de invertebrados e de plantas em ecossistemas limnicos subtropicais - Pereira, Marcos Wenceslau de Oliveira (2017)
Currently, the biological diversity of different ecosystems worldwide is jeopardized. Several factors, including anthropic impact, are interacting and causing a change in the architecture of life in different environments of the Earth. Aquatic ecosystems, especially freshwater habitats, are very sensitive points within this web of degradation. Thus, studies focused on the fauna and flora inhabiting these places are of fundamental importance for management and conservation plans to be proposed and implemented. Unicellular eukaryotes, mainly those belonging to the Phylum Ciliophora, are widely distributed in freshwater ecosystems and could be used as environmental indicators, due to their biological and physiological characteristics (such as the rapid response that these organisms possess to the minimal changes they suffer in the habitats where they live). Peritrich ciliates are distributed in different varieties kinds of freshwater environments, being able to constitute ectosymbiotic relationships with diverse living aquatic organisms. However, studies of these epibiont organisms from the taxonomic scope, and with respect to their life cycle, and ecological characteristics are scarce in the specific literature. Thus, the central aim of the present research is to provide detailed descriptions of the morphology of peritrich ciliates (both in vivo and from fixed organisms), epibionts of invertebrates and plants in freshwater ecosystems, providing valuable information to future studies from different scientific areas, that could use this basic information as an instrument.